2018
DOI: 10.1016/j.athoracsur.2017.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Subclavian/Axillary Access for Self-Expanding Transcatheter Aortic Valve Replacement Renders Equivalent Outcomes as Transfemoral

Abstract: Major morbidity and mortality rates SCA-TAVR are equivalent to TF-TAVR. The SCA should be the preferred secondary access site for TAVR because it offers procedural and clinical outcomes comparable to TF-TAVR and applies to most patients who are not TF candidates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
87
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 103 publications
(94 citation statements)
references
References 24 publications
5
87
2
Order By: Relevance
“…In agreement with previous series patients deemed candidates for TSc approach (as for any alternative to TF) presented higher estimated surgical risk. Main factors that conditioned that risk included higher rate of previous myocardial infarction and more extent coronary artery disease what conditioned lower left ventricular ejection fraction which yields important increase in estimated surgical risk by logistic EuroSCORE .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In agreement with previous series patients deemed candidates for TSc approach (as for any alternative to TF) presented higher estimated surgical risk. Main factors that conditioned that risk included higher rate of previous myocardial infarction and more extent coronary artery disease what conditioned lower left ventricular ejection fraction which yields important increase in estimated surgical risk by logistic EuroSCORE .…”
Section: Discussionsupporting
confidence: 91%
“…In agreement with previous series [14][15][16][17][18][19]25,26] [27]. However, this score tended to over-estimate the risk in patients treated through TSc approach and needs to be interpreted with caution.…”
Section: Baseline Risk Gender Differences and Padsupporting
confidence: 88%
See 1 more Smart Citation
“…Subclavian/axillary (SCA) access is one of the most well‐studied alternative access techniques with excellent results. Gleason et al recently published a propensity‐matched series of 202 SCA and TF patients form the CoreValve Pivotal Trial Program and showed equivalent results for major morbidity and mortality . In this series, SCA was noted to have an incidence of 30‐day mortality of 5.4% compared to 5.9% for TF, any stroke or TIA was 7.5% compared to 5.0% for TF, and incidence of “life threatening” bleeding was 11.4% compared to 10.4% for TF.…”
Section: Discussionmentioning
confidence: 91%
“…small femoral arteries, extensive obstructive atherosclerotic disease, moderate-severe calcification, and/or severe tortuosity), alternative access sites for TAVR have included trans-apical, trans-subclavian, direct aortic, trans-carotid, and trans-caval. [8][9][10] The vast majority of these alternative access procedures are usually conducted under general anesthesia and carry higher rates of morbidity and mortality; though a selection bias in this patient population certainly exists. 8 Overall, in cases where some or even all "high risk" features are present, there is little in the literature or guidelines to help implanting physicians objectively select one particular access route over the other.…”
mentioning
confidence: 99%